Soil water availability and branch age explain variability in xylem safety of European beech in Central Europe - Greta Weithmann; Roman M. Link; Bat-Enerel Banzragch; Laura Würzberg; Christoph Leuschner; Bernhard Schuldt (Oecologia, 2022)
Xylem embolism resistance has been identified as a key trait with a causal relation to drought-induced tree mortality, but not much is known about its intra-specific trait variability (ITV) in dependence on environmental variation. We measured xylem safety and efficiency in 300 European beech (F agus sylvatica L.) trees across 30 sites in Central Europe, covering a precipitation reduction from 886 to 522 mm year −1 . A broad range of variables that might affect embolism resistance in mature trees, including climatic and soil water availability, competition, and branch age, were examined. The average P 50 value varied by up to 1 MPa between sites. Neither climatic aridity nor structural variables had a significant influence on P 50 . However, P 50 was less negative for trees with a higher soil water storage capacity, and positively related to branch age, while specific conductivity ( K s ) was not significantly associated with either of these variables. The greatest part of the ITV for xylem safety and efficiency was attributed to random variability within populations. We conclude that the influence of site water availability on P 50 and K s is low in European beech, and that the high degree of within-population variability for P 50 , partly due to variation in branch age, hampers the identification of a clear environmental signal.